Dictionary of scientific biography. [Volumes 15 & 16] - Gillispie, Charles Coulston; American Council of Learned Societies (New York : Charles Scribner's Sons, 1981)
Contains articles about the professional lives of scientists not included in the previous volumes; features topical essays that examine the science of the ancient civilizations of Egypt, Japan, Mesopotamia, and the Maya; and includes a comprehensive index.
v. 15. Supplement I, Roger Adams-Ludwik Zejszner, Topical essays -- v. 16. Index.
"Published under the auspices of the American Council of Learned Societies"--P. facing t.p.
Includes bibliographical references and index.
Wilson's Senior High School.
Young Adult
Keywords: Science -- History -- Dictionaries; Scientists -- Biography -- Dictionaries; Science -- History -- Dictionaries; Scientists -- Biography -- Dictionaries